POTRET KENAKALAN TOKOH WASKITO DALAM NOVEL PERTEMUAN DUA HATI KARYA NH. DINI - Karnadi, Mita Carina; Salwa, Siti Nur (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2024)
Child delinquency is one thing that must be considered by parents. The writer is interested in researching more deeply about the delinquency of the character Waskito in the novel The Meeting of Two Hearts by Nh. Dini. The object of this research is the novel Meetings of Two Hearts by Nh. Dini. This study uses a descriptive qualitative method by describing the data encountered in the form of words and sentences. The technique used is the technique of observing and noting. The listening technique is used in listening to the novel Meeting of Two Hearts and the note-taking technique is used in writing down the sentences to be quoted in the novel. The researcher obtained the data by reading the novel in its entirety and identifying the contents of the novel based on the mischief committed by the character Waskito. The aims of this research are (1) to find out the intrinsic elements in the novels of The Meeting of Two Hearts by Nh. Dini, (2) To find out the form of mischief committed by the character Waskito in the novel Gathering of Two Hearts by Nh. Dini, (3) To find out the cause of the occurrence of the delinquency committed by the character Waskito in the novel Gathering of Two Hearts by Nh. Dini. The results showed that Waskito's delinquency was caused by family and friends factors. Waskito does not get parental love and feels jealous of his friends because his parents always pick him up and pick him up.